2019
DOI: 10.1111/jai.13949
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of bigeye tuna (Thunnus obesus) and yellowfin tuna (Thunnus albacares) caught on aggregated schools in the western equatorial Atlantic Ocean

Abstract: Summary The present study aims to characterize and compare the diet of bigeye and yellowfin tunas caught on aggregated schools in the western equatorial Atlantic Ocean. The samples were collected from January 2011 to June 2016. The tunas were measured on board and the stomachs were removed after evisceration. The stomachs were analyzed regarding their Index of Fullness and the importance of each prey in the diet was estimated by the Index of Relative Importance (IRI). The diet overlap was assessed by the Moris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Differences on the vertical distribution along tropical and temperate regions seems also to reflect in the trophic links of the viperfish. While C. sloani represents one of the most important prey items of epipelagic predators in several locations 10 , 35 , 36 , 52 , previous studies addressing the trophic ecology of epipelagic predators along the WTA do not mention a trophic relationship with the viperfish 9 , 53 . Moreover, SIA results do not evidence a well-defined trophic relationship between the viperfish and potential epipelagic predators.…”
Section: Discussionmentioning
confidence: 99%
“…Differences on the vertical distribution along tropical and temperate regions seems also to reflect in the trophic links of the viperfish. While C. sloani represents one of the most important prey items of epipelagic predators in several locations 10 , 35 , 36 , 52 , previous studies addressing the trophic ecology of epipelagic predators along the WTA do not mention a trophic relationship with the viperfish 9 , 53 . Moreover, SIA results do not evidence a well-defined trophic relationship between the viperfish and potential epipelagic predators.…”
Section: Discussionmentioning
confidence: 99%
“…Diet analysis using the stomach content of bigeye tuna has been an efficient approach and widely investigated for samples from the western Indian Ocean (Kornilova, 1980;Bashmakov et al, 1991;Potier et al, 2004), southern Africa (Shannon, 1987), the tropical Atlantic (Ménard et al, 2000;Vaske-Jr et al, 2012;da Silva et al, 2019), the central Pacific (Grubbs et al, 2001;Ménard et al, 2006), the west Pacific (Ohe and Moriguchi, 2009), and eastern Australia (Young et al, 2010). These studies have indicated that teleosts, cephalopods, and crustaceans are the three main diet groups consumed, and teleosts have been consistently reported to account for the highest proportion of the diet.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the few samples with above limit Cadmium that were detected on skipjack products; it has recently been reported: 1) diet of the tuna is a driving factor on the type of element accumulation ( Houssard et al., 2019 ), 2) Skipjack is merely an epipelagic species like Yellowfin, which has been found to feed on small fish, squids, phytoplankton, etc. ( da Silva et al., 2019 ), 3) Phytoplankton up take Cadmium is similar to phosphate ( Morel et al., 2020 ), and 4) Cadmium has a nutrient like vertical distribution that resembles much the dissolved organic/inorganic phosphate ( Ormaza-González, 1990 ; de Baar et al., 1994 ) and correlate linearly with a high r 2 . It could be deemed that these facts could explain the few cases found, which only represent 0.47 % of the samples.…”
Section: Resultsmentioning
confidence: 99%